Understanding the NaCl-dependent behavior of hydrogen production of a marine bacterium, Vibrio tritonius - Al-saari, Nurhidayu; Amada, Eri; Matsumura, Yuta; Tanaka, Mami; Mino, Sayaka; Sawabe, Tomoo (PeerJ, 2019)
Biohydrogen is one of the most suitable clean energy sources for sustaining a fossil fuel independent society. The use of both land and ocean bioresources as feedstocks show great potential in maximizing biohydrogen production, but sodium ion is one of the main obstacles in efficient bacterial biohydrogen production. Vibrio tritonius strain AM2 can perform efficient hydrogen production with a molar yield of 1.7 mol H2/mol mannitol, which corresponds to 85% theoretical molar yield of H2 production, under saline conditions. With a view to maximizing the hydrogen production using marine biomass, it is important to accumulate knowledge on the effects of salts on the hydrogen production kinetics. Here, we show the kinetics in batch hydrogen production of V. tritonius strain AM2 to investigate the response to various NaCl concentrations. The modified Han–Levenspiel model reveals that salt inhibition in hydrogen production using V. tritonius starts precisely at the point where 10.2 g/L of NaCl is added, and is critically inhibited at 46 g/L. NaCl concentration greatly affects the substrate consumption which in turn affects both growth and hydrogen production. The NaCl-dependent behavior of fermentative hydrogen production of V. tritonius compared to that of Escherichia coli JCM 1649 reveals the marine-adapted fermentative hydrogen production system in V. tritonius. V. tritonius AM2 is capable of producing hydrogen from seaweed carbohydrate under a wide range of NaCl concentrations (5 to 46 g/L). The optimal salt concentration producing the highest levels of hydrogen, optimal substrate consumption and highest molar hydrogen yield is at 10 g/L NaCl (1.0% (w/v)).